(untitled) (Indian Journal of Animal Production and Management, 2018)
A bench mark survey was conducted to collect the base line information from the goat rearers regarding various housing management practices with special reference to Pantja goats of Udham Singh Nagar and Nainital districts of Tarai region of the Uttarakhand during a period of two years (April, 2015 to March, 2017). The results of present study revealed that maximum goat rearers (59.69%) maintained the flock within a shed near to own residences (79.84%). Majority of goat rearers (62.79%) had kachcha floor and used temporary type of roof (84.65%). 64.50 % goat rearers had a practice to house all categories of goats in one shed and 69.77% goat keepers housed the goats at night. 78.29 % goat rearers did not have feeder in the goat shed and 69.46% goat rearers had no drainage system in the shed. The effect of districts on type of house, type of flooring, feeder in goat shed, drainage system and sanitation condition of shed were found significant while its effect on rest of the housing practices was non-significant. It can be concluded from the study that the scientific housing practices are generally not followed by most of the goat keepers. Creation of awareness regarding scientific housing practices will help in improving the productivity of goats and income of the goat keepers.